The Effect of Fatty Acids and BSA Purity on Synthesis and Properties of Fluorescent Gold Nanoclusters - Andrýsková, Pavlína; Šišková, Karolína Machalová; Michetschlägerová, Šárka; Jiráková, Klára; Kubala, Martin; Jirák, Daniel (Nanomaterials (Basel, Switzerland), 2020)
Fluorescent gold nanoclusters (AuNCs) are envisaged as a novel type of fluorophores. This work reports on the first comparative study investigating the effect of presence/absence/abundance of fatty acids (namely palmitic acid, PA) or other substances (like glycoproteins and globulins) in the protein (bovine serum albumin, BSA) on synthesis and properties of the final AuNCs. The most popular template (BSA) and microwave (MW)-assisted synthesis of AuNCs have been intentionally chosen. Our results clearly demonstrate that the fluorescent characteristics (i.e., fluorescence lifetime and quantum yield) are affected by the fatty acids and/or other substances. Importantly, the as-prepared AuNCs are biocompatible, as determined by Alamar Blue assay performed on Hep G2 cell line.